The Effect of Financial Management Practices on Performance of SMEs in Sri Lanka - HMDN, Somathilake; C, Pathirawasam (International Journal of Scientific Research and Management (IJSRM), 2020)
Small and Medium Enterprises (SMEs) play an important role in every developing country contributing to the growth of the economy in many ways. The aim of this study is to identify the effect of financial management practices on performance of SMEs in Sri Lanka: Special Reference to North Central Province (NCP). Working capital management practices, Investment appraisal practices, Capital structure management practices, financial reporting & analysis practices and Accounting information system practices were identified as independent variables and Performance of SMEs was identified as the dependent variable of this study. All SMEs (nearly 2000 SMEs) operating in NCP during the year 2019 was identified as the population of this study. Out of that, 322 SMEs were selected as the sample based on disproportionate stratified random sampling method and final sample was 245 manufacturing, service and trade SMEs operating in NCP. Data was collected through a structured questionnaire distributed among SMEs functioning in NCP. Descriptive statistics and inferential statistics like Pearson correlation analysis and multiple regression analysis were used to analyze data using the SPSS package. Results of the study revealed that there is a positive effect of financial management practices on performance of SMEs. Among financial management practices, working capital management practices and capital structure management practices have a significant positive effect on SMEs performance.Keywords: Capital structure, Financial Management, Performance, Small and Medium Enterprises, Sri Lanka, Working capital.